(untitled) (Research, Society and Development, 2022)
The present controlled analytical, prospective, double-blind study aimed to (1) verify if adults with visual stress, assessed by an eye-tracker, when compared to a control group, show differences in eye-movements during reading texts and (2) provide evidences of internal structure validity for the Questionnaire for Characterization of Visual and Learning Difficulties. Participated adults with visual stress (GEV; n = 16) paired with a control group without visual stress (CG; n = 24). For the analysis of the eye-tracker with infrared technology, each participant read 16 texts, presented randomly, with the GEV performing 239 readings and the GC 342 readings. For the questionnaire validation study, the records of 291 consecutive adults were retrospectively added. The results showed significant differences between the GEV and the GC, namely: Fixation, Regression, Fixation Duration, Directional Attack, Reading Rate, Reading Efficiency, Cross-correlation, Fixation Anomalies, and Binocular Anomalies. These results demonstrate that the GEV, when compared to the GC, presented a less efficient oculomotricity, with worse cross-correlation and a greater number of Binocular Anomalies, which evidences movements in opposite directions and difficulty in binocular coordination. The Questionnaire for Characterization of Visual and Learning Difficulties proved to be adequate in the factor analysis, which adds evidence of internal structure validity. These findings reinforce that readers with visual stress had oculomotor difficulties in reading.